2016
DOI: 10.3389/fpsyg.2016.01826
|View full text |Cite
|
Sign up to set email alerts
|

Replication Rate, Framing, and Format Affect Attitudes and Decisions about Science Claims

Abstract: A series of five experiments examined how the evaluation of a scientific finding was influenced by information about the number of studies that had successfully replicated the initial finding. The experiments also tested the impact of frame (negative, positive) and numeric format (percentage, natural frequency) on the evaluation of scientific findings. In Experiments 1 through 4, an attitude difference score served as the dependent measure, while a measure of choice served as the dependent measure in Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…tend to also affect attitudes as well (see also [ 67 69 ]). Additionally, Barnes and colleagues [ 61 ] demonstrated that the attitude difference dependent measure that we employed in the present study predicted choice outcomes of participants who were given the option to pick one prescription drug or another.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…tend to also affect attitudes as well (see also [ 67 69 ]). Additionally, Barnes and colleagues [ 61 ] demonstrated that the attitude difference dependent measure that we employed in the present study predicted choice outcomes of participants who were given the option to pick one prescription drug or another.…”
Section: Discussionmentioning
confidence: 80%
“…For our purposes, we used attitude towards science claims to measure the impact of the various kinds of attacks directed against the claims. The basic procedure and attitude-based dependent measure used in the present studies are nearly identical to those used by Barnes, Tobin, Johnston, MacKenzie, and Taglang [ 61 ]. We chose the procedure and dependent measure used by Barnes and colleagues because they found that their attitude measures were in agreement with a choice measure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen an increased focus on the "reproducibility crisis" in science, both in science at large (Baker et al, 2016;Munafò et al, 2017; "Replication studies offer much more than technical details", 2017), and perhaps even more acutely in the psychological sciences (Open Science Collaboration, 2015). Some of the reasons behind this crisis-including flawed statistical procedures, career incentive structures that emphasize rapid production of "splashy" (i.e., unlikely) results while punishing "failed" studies, and biases inherent in the publication system-have been articulated carefully in previous work, again both generally (Szucs, 2016;Barnes, Tobin, Johnston, MacKenzie, & Taglang, 2016;Wicherts et al, 2016), and for fMRI in particular (Carp, 2012;Button et al, 2013;Poldrack et al, 2017;Szucs & Ioannidis, 2017). Among these problems, the most frequently identified, and possibly the most easily remedied, is lack of statistical power due to too-small samples.…”
Section: Introductionmentioning
confidence: 99%